Projeto de um sistema wetland francês para tratamento de efluente em um campus universitário - Souza, Gustavo Henrique Fernandes de (2021)
French constructed wetland is a biotechnology used in the treatment of effluents, where plants act as aids in the removal of pollutants present in the sewage, along with the filtering material and microorganisms. The main advantages of this system are the smaller implementation area when compared to horizontal flow wetlands or stabilization lagoon, besides not needing primary treatment. The present work aimed at designing a French built Wetland system to be used as a decentralized treatment unit for the effluent produced by a campus of the Universidade Tecnológica Federal do Paraná, Londrina campus. The work contemplated the number of students in 20 years, pre-treatment, plant dimensioning, effluent storage reservoirs, pumping system of the two reservoirs, besides all necessary calculations to perform the treatment in 5 beds, 3 in the first stage and 2 in the second stage in vertical flow with intermittent feeding.